Climate impact of stratospheric ozone recovery. Issue 11 (9th June 2013) - Bekki, S.; Rap, A.; Poulain, V.; Dhomse, S.; Marchand, M.; Lefevre, F.; Forster, P.M.; Szopa, S.; Chipperfield, M.P.
Abstract [1] Past stratospheric ozone depletion has acted to cool the Earth's surface. As the result of the phase‐out of anthropogenic halogenated compounds emissions, stratospheric ozone is projected to recover and its radiative forcing (RF‐O3 −0.05 W/m2 presently) might therefore be expected to decay in line with ozone recovery itself. Using results from chemistry‐climate models, we find that, although model projections using a standard greenhouse gas scenario broadly agree on the future evolution of global ozone, they strongly disagree on RF‐O3 because of a large model spread in ozone changes in a narrow (several km thick) layer, in the northern lowermost stratosphere. Clearly, future changes in global stratospheric ozone cannot be considered an indicator of its overall RF. The multi‐model mean RF‐O3 estimate for 2100 is +0.06 W/m2 but with a range such that it could remain negative throughout this century or change sign and reach up to 0.25 W/m2.